Kualitas Official Statistics BPS Terhadap Penggunaan Big Data sebagai Sumber Data - Pratama Rhomdoni P.I (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research examines the quality of BPS Official Statistic in integrating Big Data as a source of statistical data. The research methodology involves in-depth analysis of recent literature, critical assessment of data collection methodologies, and exploration of solutions to the challenges faced. In terms of accuracy and reliability of data, the research highlights the complexity of managing data from various heterogeneous sources. Challenges such as differences in data quality and correction methods are the main focus. The research findings indicate the necessity for BPS to develop an effective data integration framework and precise correction methods. Meanwhile, in the context of privacy and ethics, the research identifies the need for strict policies and procedures to protect individual privacy rights. In-depth understanding of the ethics of data usage, transparency in data collection, and moral considerations in data usage are also primary concerns. The research emphasizes the importance of a proactive approach to risks and impacts, as well as community involvement in decision-making processes related to privacy. This research contributes to the understanding of the complexity of using Big Data in the official statistics context and offers a holistic framework to address these challenges. The implications of the research findings can assist BPS and similar statistical agencies in enhancing data integrity, preserving privacy, and ensuring that the use of Big Data maximizes benefits for national planning and development.